Exploring the Potential of Traditional Herbs in the Management of Diabetic Retinopathy: An Overview - Singh, Soumya; Kushwaha, Poonam; Gupta, Sujeet Kumar (Drug Research, 2020)
Diabetic retinopathy is a microvascular complication in diabetes that affects eyes and is responsible for most visual impairment in diabetic patients. Diabetic retinopathy affects up to 80% of those who have had diabetes for 20 years or more. At least 90% of new cases could be reduced with proper treatment and monitoring of the eyes. The longer a person has diabetes, the higher his or her chances of developing diabetic retinopathy. Hence, it compels need for its prevention and cure. There is an increasing interest in natural products in pharmacotherapy as the chemical diversity of natural products has better matches than the diversity of synthetic compounds. The current review summarises the potential of leading traditional herbs like Azadirachta indica, Ginkgo biloba, Anisodus tanguticus, Pinus pinaster, Salvia miltiorrhiza, Stephania tetrandra and Gymnema sylvestre in the management and potential reversal of DR-related pathogenesis. It also discusses the probable mechanism of actions, which are based on epidemiological, in-vitro and in-vivo studies carried out within past few years. Graphical Abstract.
Keywords: diabetes mellitus; diabetic retinopathy; signalling mechanisms; traditional herbs